2019
DOI: 10.1177/0907568218823882
|View full text |Cite
|
Sign up to set email alerts
|

Can performing happy childhood be an occupational skill required of students?

Abstract: Lanas (2019) Can performing happy childhood be an occupational skill required of students? 0 Lanas, M. (2019). Can performing happy childhood be an occupational skill required of students?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…As previous research has shown, hugging is often seen as a good and proper thing to do, and educators usually pay positive attention when children are hugging each other (see also Laws and Davis, 2010). It seems that Maria is aware of this and is able to perform in front of the educator a more appropriate kind of touch in terms of what is expected of her in the institutional context and culture of the preschool (Lanas, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous research has shown, hugging is often seen as a good and proper thing to do, and educators usually pay positive attention when children are hugging each other (see also Laws and Davis, 2010). It seems that Maria is aware of this and is able to perform in front of the educator a more appropriate kind of touch in terms of what is expected of her in the institutional context and culture of the preschool (Lanas, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In these routinised acts, educators can assume that children already know what to do and trust them to do what is expected (Williams, 2001). Hence, the educator emphasises here children’s agency, and the touch as a conventional pattern directs children to the categories of good behaviour (Lanas, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with all performatives, the performance of child characters or ‘childhood’ which is essential for the audience’s understanding, invokes dominant discourses around them in order to be read as such (Youdell, 2006: 37). The establishment of an actor as a child character or of a moment as an enactment of the essence of childhood is then a question of ‘taking on the appropriate discursive performatives’ (Lanas, 2019: 252). Therefore the school uniform is suggestive of a child character even when it adorns the person of an older actor.…”
Section: Locating ‘Childhood’ In Tya Productionsmentioning
confidence: 99%
“…In Childhood Studies, the emphasis has been more on performativity than performance to understand how institutional discourses, for example the school-produced discourse about ‘happy childhood’ shape the experiences of children (Lanas, 2019). Though closely related, the performance of childhood is much less explored in Childhood Studies.…”
Section: Introductionmentioning
confidence: 99%